Vogel method to reduce the cost of transporting solid waste to the city of Basra - Naeem, Ali Abdel Hussein; Madi, Sabreen Nuri (Journal of Economic, Administrative and Legal Sciences, 2018)
The purpose of this research is to study the possibility of reducing the costs of transporting solid waste, using the approximate Vogel method, to reach the optimal solution. The descriptive and quantitative analysis method was used to identify solid waste collection and transport in Basra city, based on the documents and the private data records in Basra Governorate Municipality. The researcher conducted field visits to determine the sanitary landfill sites of Basra city to determine the distances and then put them electronically on the GIS program, the city mapping and the landfill sites. The research found the most important results by applying the approximate Vogel method of operation research to the process of solid waste transfer from Basra city, which proves the validity of the research hypothesis which states, "There is an effect of scientific methods on reducing the cost of solid waste transportation in Basra". The study concluded that the use of the Vogel method is useful and feasible because it achieves a financial abundance of costs for the city of Basra (11,111,140,000 IQD) compared to the actual costs incurred by conventional methods in Basra. These indicates the amount of waste in resources; because of the absence of application of scientific methods in the process of waste transfer, and therefore recommended the research in the use of scientific methods of modern applications and encourage researchers to develop the field of waste transport.